Pengaruh Pembiasaan Menghafal Juz ‘Amma Terhadap Peningkatan Aspek Afektif Siswa Pada Program Tahfidz Fase C Di SDIT Miftahul Ulum Cisurupan Garut - Fauziah, Hapsah; Rohali, Syifa (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
The Qur'an is the main obligation for every Muslim and should also be started early so that the child's mind is still clean and his memory is still strong. One form of learning the Qur'an that can be started early is Tahfidzul Qur'an. This can be realized when educational institutions such as schools have religious activities, one of which is about habituating the Juz 'Amma memorization program to students. This study uses a descriptive quantitative method because in this study the results are presented in the form of statistical figures. This quantitative research is carried out to clarify something based on data obtained from the field. The results of the study showed that the habit of memorizing Juz 'Amma in the tahfidz program had an average of 4,53 thus the average was in the interval area of 4,01-5,00 included in the category of "Very Good", this showed that the affective aspect of students increased after the teacher applied the habit of memorizing Juz 'Amma in the tahfidz program, while the affective aspect had an average of 4,7 thus the average was in the interval area of 4,01-5,00 included in the "Very Good" category, this shows that the habit of memorizing Juz 'Amma is the right solution to improve the affective aspect of students. Based on the statistical test "There is an Effect" of the habit of memorizing Juz 'Amma on the improvement of students' affective 0,20 – 0,39 while other variables that were not studied and affected the habit of memorizing Juz 'Amma were 62,5%.  Keywords: habituation; juz 'amma; Affective